Efektivitas Penggunaan Model Pembelajaran Problem Based Learning dalam Menyelesaikan Soal Garis Bilangan Bulat terhadap Kemampuan Berpikir Matematis Siswa Kelas 3 Sekolah Dasar - Unaenah, Een; Awaludin, Anas Farhan; Sukma, Frizori Rendy (MASALIQ, 2023)
This study was made to determine the effectiveness of computational thinking in solving integer line problems in third grade elementary school students. The research used is the Quasi experimental method. The research subjects were grade III elementary school students. The instrument with test questions. The results of this study used a parametric analysis test which concluded that there was an effectiveness in the application of computational thinking steps in solving integer line problems. Where the experimental class has a greater average than the control class, namely 80 > 65 with a total of 32 students in the experimental class and 36 in the control class. Based on the existing hypothesis, there are differences in the learning outcomes of the experimental class and experimental class. Furthermore, the results of the N-Gain test for the experimental class were 78.15%, and the results for the N-Gain test for the control class were 53.66%, which means that there is effectiveness in applying students' computational thinking steps in solving problems.